Teaching of Building Information Modeling (BIM) in Higher Education Institutions in Brazil: analysis of the Theses and Dissertations produced in the period from 2013 to 2020 - Bonfante, Hortência Santos Teixeira; Palmisano, Angelo; Godoy, Jeane Aparecida Rombi de (National Journal of City Management, 2024)
Building Information Modeling (BIM) has emerged as a necessary tool in the architecture, engineering, construction and operations scenario, offering an innovative and integrated approach not only for project development, but also contributing to the construction management and maintenance of buildings. . In the Brazilian context, academia has dedicated special attention to BIM, reflected in the production of theses and dissertations carried out over the last few years. This research aimed to identify the main trends and pedagogical approaches used in the productions found, presenting their strengths and advances verified in the use of this methodology, as well as the weaknesses or limiting points, based on Brazilian academic production on teaching BIM in the period from 2013 to 2020, resulting from the analysis of theses and dissertations published in the CAPES Catalog of Theses and Dissertations, which address the topic of Construction Information Modeling or Building Information Modeling in the dimension of its teaching. classifies as applied, exploratory, with a qualitative approach, using the bibliographic research method and application of the content analysis technique. It is hoped that, through the results obtained, the adoption of the BIM methodology in undergraduate courses in architecture and urbanism and related areas can be encouraged in the country.